2009
DOI: 10.1590/s0004-28032009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Terminal ileum of patients who underwent colonoscopy: endoscopic, histologic and clinical aspects

Abstract: -Context -For the diagnosis of the diseases which affect the terminal ileum, the colonoscopy allows macroscopic evaluation and the performing of biopsies. Studies with criteria for the endoscopic and histological characterization of this segment are scarce and there are still some doubts about the need of biopsies in patients with normal ileoscopy. Objective -Study the terminal ileum of patients who underwent colonoscopy considering: endoscopic and histological correlation; agreement between results of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
8
1
2
Order By: Relevance
“…In a study by Melo et al (1) performed in 2009, biopsy results of 111 cases with a normal-appearing terminal ileum were assessed. The comparison of a group with chronic diarrhea and/or abdominal pain to a group of asymptomatic patients or patients with other symptoms showed that the possibility of having mild to moderate ileitis was 2.5-fold higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Melo et al (1) performed in 2009, biopsy results of 111 cases with a normal-appearing terminal ileum were assessed. The comparison of a group with chronic diarrhea and/or abdominal pain to a group of asymptomatic patients or patients with other symptoms showed that the possibility of having mild to moderate ileitis was 2.5-fold higher.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is lined by a specialized lymphoid tissue of the immune system. Increases in lymphocytes, macrophages, and mast cells in response to luminal antigens are observed physiologically (1, 2). Diseases involving the terminal ileum may be classified as the inflammatory bowel diseases (IBD), infectious and parasitic diseases, and more rarely, neoplasia.…”
mentioning
confidence: 99%
“…Em estudo prospectivo de 111 pacientes que apresentaram ao exame endoscópico do íleo terminal normal (mucosa lisa e sem enantema), Melo et al 35 constataram que a chance de indivíduos com ileoscopia normal, portadores de dor abdominal e ou diarréia crônica, apresentar alterações histológicas foi 2,5 vezes maior em relação aos demais.…”
Section: Neoplasias Neoplasias Neoplasias Neoplasias Neoplasiasunclassified
“…Diversos autores sugerem a realização de biópsias do íleo terminal de aspecto endoscópico normal em pacientes com diarréia crônica e ou dor abdominal 5,31,[33][34][35][36] , pois a partir do estudo histológico desses casos foi possível o diagnóstico de enfermidades como doença de Crohn 34,36 , tuberculose intestinal 31 , citomegalovirose 33 e microsporidíase 34 . Por outro lado, Yusoff et al 37 e Silva et al 38 verificaram que a avaliação microscópica de pacientes com diarréia crônica e ileoscopia normal não contribuiu para o diagnóstico de seus pacientes.…”
Section: Considerações Finais Considerações Finais Considerações Finaunclassified
“…However, the clinical setting and the indication for the procedure is of paramount importance and may be correlated with the diagnostic yield when performing biopsies in a suitable setting [9][10][11]. Thus, TI biopsies may be of greatest value for patients who undergo endoscopy for known or strongly suspected Crohn's disease [12][13][14].…”
Section: Introductionmentioning
confidence: 99%